2015
DOI: 10.1590/1519-6984.05914
|View full text |Cite
|
Sign up to set email alerts
|

Feather mites of Calidris fuscicollis (Aves: Scolopacidae) in Brazil

Abstract: During the period 2010-2012, eighty individuals of Calidris fuscicollis (Vieillot, 1819) were collected on the southern coast of Rio Grande do Sul, Brazil, with the objective of determining the presence of feather mites. Of the 80 birds examined, 32.5% were infested by mites, identified as Avenzoaria calidridis (Oudemans, 1904) Palavras-chave: ácaros plumícolas, Avenzoariidae, Pterolichidae, Alloptidae, maçarico-de-sobre-branco.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…2012;Hernandes 2012;2013a, 2013b2014;Valim 2012, 2014;Jardim et al 2012;Enout et al 2012;2015a, 2015bMironov and Hernandes 2014;Mironov et al 2015;2016;Hernandes and OConnor 2015;Hernandes and Mironov 2015;Gomes et al 2015;Hernandes and Pedroso 2016). Including the data from the present study, the feather mites recorded in Brazil total 272 named species associated with 306 bird species.…”
Section: Bird Species Excludedmentioning
confidence: 65%
“…2012;Hernandes 2012;2013a, 2013b2014;Valim 2012, 2014;Jardim et al 2012;Enout et al 2012;2015a, 2015bMironov and Hernandes 2014;Mironov et al 2015;2016;Hernandes and OConnor 2015;Hernandes and Mironov 2015;Gomes et al 2015;Hernandes and Pedroso 2016). Including the data from the present study, the feather mites recorded in Brazil total 272 named species associated with 306 bird species.…”
Section: Bird Species Excludedmentioning
confidence: 65%
“…In Brazil, feather mites were previously reported from only two birds of the order Charadriiformes: five species from the southern lapwing, Vanellus chilensis (Molina, 1782) (Charadriidae) (Pedroso et al 2015) and three species from the white-rumped sandpiper, Calidris fuscicollis (Vieillot, 1819) (Scolopacidae) (Gomes et al 2015). Since there are 92 charadriiform birds occurring in Brazil (Pacheco et al 2021), certainly many more feather mites remain to be described and reported from these hosts.…”
Section: Introductionmentioning
confidence: 99%